Capitellum excision: Mechanical implications and clinical consequences. Issue 2 (20th November 2013) - Root, Cassie Gyuricza; Meyers, Kathleen; Wright, Timothy; Hotchkiss, Robert
Abstract Controversy exists regarding the optimal treatment of isolated fractures of the capitellum that are not amenable to open reduction and internal fixation. Excision of the capitellum could result in instability of the elbow, though only limited the clinical or laboratory evidence exists to support this outcome. The aim of our study was to determine if capitellum excision leads to significant instability by measuring the relative change in varus–valgus displacement of the elbow. The varus–valgus displacement was recorded in 11 cadaveric elbows before and after isolated excision of the capitellum. Specimens were testing in varus‐loaded and valgus‐loaded positions with and without a 1 kg weight on the forearm. The varus–valgus displacement at the elbow was measured using a 3D motion capture system. Capitellum excision did not significantly change varus–valgus displacements in either the adducted, varus, or valgus position of the elbow (p = 0.80, p = 0.28, p = 0.51). Furthermore, the addition of the 1 kg external functional load to the forearm did not produce a significant change in the varus and valgus loaded positions (p = 0.16, p = 0.36). Our results demonstrate that excision of the capitellum in the setting of intact ligamentous structures does not result in significant instability in either the adducted varus loaded or valgus loaded positions of the elbow. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:346–350, 2014.